Staggered difference-in-differences in gravity settings: Revisiting the effects of trade agreements - Arne J. Nagengast; Yoto Yotov (Deutsche Bundesbank, 2023)
We nest an extended two-way fixed effect (ETWFE) estimator for staggered difference-in-differences within the structural gravity model. To test the ETWFE, we estimate the effects of regional trade agreements (RTAs). The results suggest that RTA estimates in the current gravity literature may be biased downward (by more than 50% in our sample). Sensitivity analyses confirm the robustness of our main findings and demonstrate the applicability of our methods in different settings. We expect the ETWFE methods to have significant implications for the estimates of other policy variables in the trade literature and for gravity regressions on migration and FDI flows.
urn:nbn:de:101:1-2023112813573982258379
Keywords: C13; C23; F10; F13; F14; 330; Staggered Difference-in-Differences; Gravity Model; Trade Agreements